Dynamic Response Calculation Algorithm for Floating Offshore Wind Turbines Based on a State-Space Method of Transfer Function - Wei, Li; Sheng-xiao, Zhao; Kun, Liu; Hong-chao, Lu; Tian-hui, Fan (Frontiers in Energy Research, 2022)
Cummins equation is commonly applied to describe the motion of floating structures. Because of the convolution term, the efficiency of calculation is low and the error accumulation problems in numerical integration calculation are serious. For those reasons, a dynamic response analysis method of floating structures based on state-space model is proposed. The method uses the state-space method to replace force-to-motion relationship of Cummins equation, i.e., transfer function, which transforms the problem of calculating the dynamic response into obtaining the output of the state-space model. The method is easy to implement and avoids the problems caused by the presence of the convolution term.